Travel and Tourism Management System Bangladesh (Beriye Pori) - Zubairy, Mahmudur Rahman (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.